2007
DOI: 10.1128/iai.01606-06
|View full text |Cite
|
Sign up to set email alerts
|

InactivatedFrancisella tularensisLive Vaccine Strain Protects against Respiratory Tularemia by Intranasal Vaccination in an Immunoglobulin A-Dependent Fashion

Abstract: Francisella tularensis is a gram-negative intracellular bacterium that is considered to be a potential category A biological weapon due to its extreme virulence. Although vaccination with the attenuated live vaccine strain (LVS) of F. tularensis can protect against lethal challenge, use of inactivated or subunit forms as vaccine candidates for induction of protective antibody responses has not been fully evaluated. In the present study, we examined whether immune protection in the lung could be stimulated by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 36 publications
5
87
1
2
Order By: Relevance
“…tularensis replicates intracellularly, and thus the role of humoral immunity against this pathogen has been controversial; however, significant contributions of the humoral response in F. tularensis infection are supported by a growing body of literature (46)(47)(48)(49)(50)(51)(52). The fact that passive administration of LVS-VϩMPL immune sera fully protected mice against challenge with F. tularensis LVS (data not shown) and extended the mean time to death significantly in mice challenged with F. tularensis Schu S4 by the s.c. route, but not by the i.n.…”
Section: Discussionmentioning
confidence: 96%
“…tularensis replicates intracellularly, and thus the role of humoral immunity against this pathogen has been controversial; however, significant contributions of the humoral response in F. tularensis infection are supported by a growing body of literature (46)(47)(48)(49)(50)(51)(52). The fact that passive administration of LVS-VϩMPL immune sera fully protected mice against challenge with F. tularensis LVS (data not shown) and extended the mean time to death significantly in mice challenged with F. tularensis Schu S4 by the s.c. route, but not by the i.n.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, adoptively transferred serum Abs have limited efficacy if given later than 48 h after infection. It is worth mentioning that in vaccinated mice, mucosal Abs such as IgA in addition to Ag-specific T cells may also contribute to overall protection (19). We are currently investigating the specific role of mucosal Abs in providing a first line defense against pulmonary tularemia.…”
Section: Discussionmentioning
confidence: 99%
“…These include infections induced with influenza virus [22], Streptococcus pneumoniae [23][24][25], Francisella tularensis [26] and Yersinia pestis [Kumar D, Metzger DW, Unpublished Data]. We and others have repeatedly found that intranasal treatment of mice with IL-12 leads to increases in expression of both Th1-and Th2-associated antibodies in the serum [9][10][11][12][13][14] as well as in the lung [22][23][24][25][26][27]. In a typical experiment, mice are inoculated intranasally with vaccine only or vaccine plus IL-12.…”
Section: For Reprint Orders Please Contact Reprints@expert-reviewscommentioning
confidence: 99%